2021
DOI: 10.3390/brainsci11101355
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Standardized Cognitive-Behavioural Therapy and an Additional Mindfulness-Based Training on Interoceptive Abilities in a Depressed Cohort

Abstract: Background: Interoceptive accuracy and sensibility are decreased in depressive samples. However, different studies showed that cognitive-behavioural therapy (CBT) and mindfulness interventions are promising approaches to improve interoceptive abilities. Based on these findings, the study aims to investigate the pre–post effect of CBT in a depressive sample. Additionally, we examined the effect of mindfulness-based stress reduction (MBSR) training in the context of CBT. Methods: Sixty depressive patients were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…A growing body of studies showed increased interoceptive abilities due to diverse interventions of various lengths, such as self-focused procedures ( Weisz et al, 1988 ; Tsakiris et al, 2011 ; Ainley et al, 2012 ; Ainley and Tsakiris, 2013 ; Pollatos et al, 2016 ), mindfulness-based interventions (e.g., Bornemann et al, 2014 ; Parkin et al, 2014 ; Bornemann and Singer, 2017 ; Fischer et al, 2017 ), floating ( Feinstein et al, 2018 ), power posing ( Weineck et al, 2019 ), or cognitive behavioral therapy in depressive patients ( Karanassios et al, 2021 ). Concerning the effects of mindfulness-based interventions on interoceptive abilities, previous findings are incongruent.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of studies showed increased interoceptive abilities due to diverse interventions of various lengths, such as self-focused procedures ( Weisz et al, 1988 ; Tsakiris et al, 2011 ; Ainley et al, 2012 ; Ainley and Tsakiris, 2013 ; Pollatos et al, 2016 ), mindfulness-based interventions (e.g., Bornemann et al, 2014 ; Parkin et al, 2014 ; Bornemann and Singer, 2017 ; Fischer et al, 2017 ), floating ( Feinstein et al, 2018 ), power posing ( Weineck et al, 2019 ), or cognitive behavioral therapy in depressive patients ( Karanassios et al, 2021 ). Concerning the effects of mindfulness-based interventions on interoceptive abilities, previous findings are incongruent.…”
Section: Introductionmentioning
confidence: 99%
“…Depression was reported to have a lower interoception, but was positively correlated for the IS questionnaire. (Karanassios et al, 2021). We suggested that individuals with depression exhibited diffused BSM of pitched sound perception in previous study (Daikoku et al, 2023).…”
Section: Introductionmentioning
confidence: 61%
“…Here, the authors found that participants with depression had a significant decrease in depression symptoms, and an increase in trait mindfulness and interoceptive abilities (heartbeat tracking task scores, task-related confidence ratings, and scores on the Body Awareness subscale of the Body Perception Questionnaire), following the four-week CBT programme. Contrary to the authors’ expectations, Karanassios and colleagues [ 26 ] found that CBT with additional mindfulness-based stress reduction training did not have any additional benefits for depressive symptoms, trait mindfulness, nor interoceptive abilities.…”
Section: Clinical Researchmentioning
confidence: 79%
“…In a different clinical context, Karanassios and colleagues [ 26 ] compared the effects of a standardised cognitive behavioural therapy (CBT) against CBT with an additional mindfulness-based stress reduction training programme on interoceptive abilities and depressive symptoms in adults with depression. Here, the authors found that participants with depression had a significant decrease in depression symptoms, and an increase in trait mindfulness and interoceptive abilities (heartbeat tracking task scores, task-related confidence ratings, and scores on the Body Awareness subscale of the Body Perception Questionnaire), following the four-week CBT programme.…”
Section: Clinical Researchmentioning
confidence: 99%